Sensory shelf life estimation of food products - Hough, Guillermo (CRC Press / Taylor & Francis, 2010)
Evaluating food consumers' sensory perception is a key factor in determining the shelf-life of many food products. This book addresses sensory shelf life of food and explains how to design a shelf life estimation experiment. It also includes the code and instructions to perform calculations using the freely distributed R statistical package